ETNOMATEMATIKA INDUSTRI RUMAH TANGGA KERUPUK BASAH DI MASYARAKAT DESA JONGKONG KIRI KECAMATAN JONGKONG KABUPATEN KAPUAS HULU - Anisa Novita Sari; Ahmad Yani T; Rustam Rustam; Bistari Bistari; Revi Pasaribu (Journal of Educational Review and Research, 2023)
ABSTRACTThis study is a study using mathematical concepts in the production of wet crackers (temet). Subsequently, this study describes the diversity of wet cracker products (temet) and by referring to ethnomathematical aspects: counting, positioning, measuring, designing, and describing wet cracker products (temet). It aims to explore the mathematical concept of The research was conducted in Jongkong Kiri Village, Jongkong District, Kapuas Hulu District. The form of this study is qualitative because of the questions involved in the study. The result of this research is that there is an ethnomathematical activity in the process of making the wet he cracker product (temet). According to Bishop (1988), the activities of all people play an important role in the development of mathematical ideas. Bishop also pointed out that there are six basic activities that can be considered in folk mathematics: counting, locating, measuring, designing, playing, and explaining. Based on human observations, each product that makes up Kapuas Hulu's signature food, wet crackers (temets), has five elements: counting, locating, measuring, designing, and describing. There are two ethno-mathematical activities.